Metabolic engineering of Escherichia coli for production of (2S, 3S)-butane-2, 3-diol from glucose. Issue 1 (December 2015) - Chu, Haipei; Xin, Bo; Liu, Peihai; Wang, Yu; Li, Lixiang; Liu, Xiuxiu; Zhang, Xuan; Ma, Cuiqing; Xu, Ping; Gao, Chao
Abstract Background Butane-2, 3-diol (2, 3-BD) is a fuel and platform biochemical with various industrial applications. 2, 3-BD exists in three stereoisomeric forms: (2R, 3R )-2, 3-BD, meso -2, 3-BD and (2S, 3S )-2, 3-BD. Microbial fermentative processes have been reported for (2R, 3R )-2, 3-BD andmeso -2, 3-BD production. Results The production of (2S, 3S )-2, 3-BD from glucose was acquired by whole cells of recombinantEscherichia coli coexpressing the α-acetolactate synthase andmeso -butane-2, 3-diol dehydrogenase ofEnterobacter cloacae subsp.dissolvens strain SDM. An optimal biocatalyst for (2S, 3S )-2, 3-BD production, E. coli BL21 (pETDuet–PT7 –budB –PT7 –budC ), was constructed and the bioconversion conditions were optimized. With the addition of 10 mM FeCl3 in the bioconversion system, (2S, 3S )-2, 3-BD at a concentration of 2.2 g/L was obtained with a stereoisomeric purity of 95.0 % using the metabolically engineered strain from glucose. Conclusions The engineeredE. coli strain is the first one that can be used in the direct production of (2S, 3S )-2, 3-BD from glucose. The results demonstrated that the method developed here would be a promising process for efficient (2S, 3S )-2, 3-BD production.